How does international monetary leadership end? The Sterling Area revisited - Alan De Bromhead; David Jordan; Francis Kennedy; Jack Seddon (Queen's University Centre for Economic History (QUCEH), 2021)
How does international monetary leadership end? This paper examines the decline of the Sterling Area between 1945 and 1979 to understand the process of international economic disintegration. Using an original cross-national panel dataset, we conduct survival analysis which systematically evaluates a comprehensive set of economic and political factors about when and why countries chose to leave the Sterling Area. We find that membership of the Sterling Area was determined by multidimensional aspects. Our results highlight the significance of international economic and geopolitical factors, such as trade and diplomatic alignment, on the decision to leave. However we also find that domestic political and historical factors, such as democracy and imperial legacy, played a role in the Sterling Area's unravelling. Finally, we use our results to examine the experience of individual countries and their decisions to leave the Sterling Area. Revisiting this history of a gradually dissolving economic order, played out in the shadow of Britain's waning imperial and economic power, has cautionary implications for the future of the US dollar order.
Keywords: N10; F02; F22; F33; 330; The Sterling Area; international monetary regime; internationalcurrency; sterling; decline; disintegration